Alterations in the membrane-associated proteome fraction of alveolar macrophages in sarcoidosis - Kjellin, Hanna; Silva, Ernesto; Branca, Rui; Eklund, Anders; Jakobsson, Per-Johan; Grunewald, Johan; Wheelock, Åsa M (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Alveolar macrophages are implicated in the pathogenesis of lung sarcoidosis. Their interaction with T-cells leads to an inflammatory response that may either resolve within 2 years, or become chronic with an increased risk to develop lung fibrosis. Objective: To perform quantitative profiling of the membrane-associated proteome of alveolar macrophages in sarcoidosis patients and healthy individuals to identify specific proteins and pathways involved in sarcoidosis pathology. Methods: Differential proteomic analysis was performed on iTRAQ (isobaric Tag for Relative and Absolute Quantitation) labeled samples using tandem mass spectrometry. Subsequently, uni- and multivariate statistical analyses and pathway- and network analyses were performed. Results: Eighty proteins were differentially expressed between healthy and sarcoidosis patients. Down-stream pathway analysis confirmed our recent reports of up-regulation of two phagocytotic pathways: Fcγ receptor-mediated phagocytosis and clathrin-mediated endocytosis signaling. An additional pathway, pyruvate metabolism, was found to be up-regulated in sarcoidosis patients. The oxidative phosphorylation pathway was differentially expressed in subgroups of sarcoidosis, with up-regulation in Löfgren’s patients and down-regulation in non-Löfgren’s patients. Conclusion: This unprecedented proteome profiling of the membrane-associated fraction of alveolar macrophages confirmed previous findings of alterations in phagocytotic pathways due to sarcoidosis, as well as indicated a differential dysregulation of the oxidative phosphorylation pathway related to disease outcome in sarcoidosis.